Local government finance in Japan : Can irresponsible borrowing be avoided? - Naoyuki Yoshino; Frank Robaschik (Universität Duisburg-Essen, Forschungsinstitut für Wirtschaftliche Entwicklungen im Pazifikraum (FIP), 2004)
Rapidly rising local government debt in Japan presents a nontrivial addition to the central government debt. The planned replacement of the approval system for local government bor- rowing by a 'consultation system' in FY 2006 does not remove the implicit central govern- ment guarantee for local debt and thus the moral hazard involved in the system. Given all the risks associated with high debt levels (crowding out, inflation, potential insustainability) and the bad selection of projects financed under the current system, we suggest to restrict local government borrowing to user based revenue bonds, where investors receive the future revenue of the project and have an incentive to carefully select and monitor the projects they finance. In a generation model we show that this not only improves the sustainability of local government debt, but that it is highly likely that the debt will be sustainable.
Keywords: 330; Government debt; sustainability; local government borrowing; local finance; Japan; generation model; government bonds; user based revenue bonds; Kommunalverschuldung; Gemeindefinanzen; Haushaltskonsolidierung; Projektfinanzierung; Finanzföderalismus; Japan